Improving Physiological Factors and Plasmid Stability of DE3 Host System - Mallu, Maheswara Reddy (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The purpose of the study delineates the growth and plasmid stability of DE3 host system. Methods: Different concentrations of drugs, chemicals, and various frequencies of radiations were subjected to the host system to verify the colony forming units, along with plasmid concentration and stability. Results: Among chemicals, acridine orange showed highest effect on growth of DH5a, while among the drugs, danthrone showed maximum effect on the growth of the organism. Radio frequency of 2GHz and low-intensity microwave radiation were recorded as highest inhibitory effects. However, there is no significant effect in growth that was observed in exposure to UV rays. Conclusion: The present work discussed that, the effect of drugs, chemicals, radio frequency, and microwave radiation has a huge effect not only on growth of organism but also concentration and stability of plasmid.